YURISDIKSI INTERNASIONAL PENANGGULANGAN PEROMPAKAN dI LAUT LEPAS - dwi Utami, Asri -; Muslimah, Siti; Torry Satriyo Kusumo, Ayub (Yustisia, 2014)
AbstractThis research aims to determine the jurisdiction concerning piracy on the high seas by international law. This research is a legal research with prescriptive characteristic use a statute approach and conceptual approach. The legal sources used are primary and secondary materials later are analyzed by a deductive method and legal interpretation. The results show that there has been international law rules which can be used as the basis for all states to apply their jurisdiction to the piracy. These rules are the convention on the high Seas 1958 (chS 1958), United Nations convention on the Law of the Sea 1982 (UNcLOS 1982), and the convention for the Suppression of Unlawful Acts Against the Safety of Maritime Navigation 1988 (SUA 1988). Instead of these international rules, some codes and guidances concerning combating piracy are also concluded by international organizations.Keywords : International Jurisdiction, Piracy, Law of The SeaAbstrakPenelitian ini bertujuan untuk mengetahui penerapan yurisdiksi terhadap perompakan di laut lepas menurut hukum internasional. Penelitian ini merupakan penelitian hukum yang bersifat preskriptif dengan pendekatan perundang-undangan dan pendekatan konseptual. Bahan hukum yang digunakan adalah bahan hukum primer dan bahan hukum sekunder yang selanjutnya dianalisis secara deduktif dan menggunakan interpretasi hukum. Hasil penelitian menjelaskan bahwa terdapat aturan-aturan hukum internasional yang dapat digunakan sebagai yurisdiksi untuk penegakan perompakan yaitu convention on the high seas 1958 (CHS 1958), United Nations convention on the Law of the Sea 1982 (UNCLOS 1982), convention for the Suppression of Unlawful Acts Against the Safety of Maritime Navigation 1988 (SUA 1988), dan beberapa pedoman dan aturan yang dikeluarkan oleh organisasi internasional untuk penegakan perompakan.Katakunci : yurisdiksi Internasional, Perompakan, Hukum Laut Internasional